2018
DOI: 10.1142/s0217751x18501014
|View full text |Cite
|
Sign up to set email alerts
|

Quark–antiquark entropic force and diffusion constant in a Yang–Mills-like theory

Abstract: The entropic force experienced by a moving quarkonia in a plasma, is computed in a hyperscaling violation background by holography approach. In that case, the axis of the moving quarkonia has an arbitrary angle with wind. We use the results for HSV parameters which obtained in our paper [1] as appropriate values satisfying condition ImV QQ < 0. We will show that, in this background the entropic force of the meson shows a decreasing behaviour corresponds to increasing dissociation length. Results of this paper … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…It was found that the entropy increases with the inter-quark distance, and the peak of the entropy emerges when the U-shaped string stretched between the touches the horizon of the black hole. Subsequently, there have many attempts to address the entropic force in this direction [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the entropy increases with the inter-quark distance, and the peak of the entropy emerges when the U-shaped string stretched between the touches the horizon of the black hole. Subsequently, there have many attempts to address the entropic force in this direction [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…After [64], several times the entropic force was calculated by using the holographic method. For example, the entropic force was studied for a moving [65] and a rotating quarkonium [66], and a moving dipole in a Yang-Mills like theory [67]. Also, the chemical potential effect [68], R 2 and R 4 corrections [69] and the effect of the deformation parameter [70] on the entropic force are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto et al, calculating for the first time the entropic force associated with the heavy quark pair using the AdS/CFT correspondence [28], showed that the entropy increases with the inter-quark distance and the peak of the entropy depends on the nature of deconfinement and emerges near the transition point. After those, the entropic force was calculated by using this method several times, for example, for a moving [29] and rotating quarkonium [30], a moving dipole in a Yang-Mills like theory [31], for the chemical potential effect [32], R 2 and R 4 corrections [33] and for the effect of deformation parameter [34].…”
mentioning
confidence: 99%